Theory of Mind and Its Elusive Structural Substrate - Lizcano-Cortés, Fernando; Rasgado-Toledo, Jalil; Giudicessi, Averi; Giordano, Magda (Frontiers in Human Neuroscience, 2021)
Is brain structure related to function? Can one predict the other? These are questions that are still waiting to be answered. We are interested in the relation between brain structure and theory of mind (ToM). ToM is defined as the ability to attribute mental states to others. Previous studies have observed correlations between performance on ToM tasks, and grey-matter size/volume in dorsomedial prefrontal cortex (dmPFC), temporoparietal junction (TPJ) and precuneus (PCu). Despite these findings, there are concerns about false positive results and replicability issues. In this study we used two different tasks to evaluate ToM, Reading the Mind in the Eyes Test (RMET), and the Short Story Task (SST). Performance in these tasks was correlated to brain anatomy measures including voxel-based morphometry (VBM) and cortical thickness (CT) analysis, from ninety-one neurotypical participants. High-resolution structural brain images were acquired, and whole-brain and region of interest (ROI) analyses were implemented. The analyses did not show statistically significant associations between ToM performance and brain structural measures after correction.These results do not replicate a previous study (Sato et al., 2016). Significant associations between performance on ToM tests and a widespread array of regions loosely associated with ToM were observed only for whole brain uncorrected analysis analysis (p < 0.001). We tested two different ToM tests, two different softwares for VBM and CT. Consequently, these results suggest that if the population is neurotypical and homogenous, it is unlikely that a reliable association between brain anatomy measures and ToM performance, may be found.